Pendampingan Guru Madrasah Ibtidaiyah dalam Penggunaan Platfrom Merdeka Mengajar pada Kurikulum Merdeka Belajar - suhelayanti, Suhelayanti; Syamsiah, Syamsiah; Muttaqin, Muttaqin; Zalila, Zilan; Syahputra, Irwanda; Agsain, Hafizah; Mulyana, Rita; Zaiyar, M. (Penerbit Goodwood, 2024)
Purpose: Not many madrasah teachers throughout Aceh have utilized PMM as well as madrasah teachers in Langsa City, PMM is a platform created by the Ministry of Education and Culture which contains the concept and implementation of an independent teaching curriculum. Through this PMM, it is very helpful for teachers in implementing the curriculum.. Research methodology: Pengabdian ini mengadopsi metodelogi Community Based Research melalui tiga skema pengabdian yaitu Persiapan- pelaksanaan- evaluasi dan pelaporan. Instrumen dalam pengabdian ini berupa tes, observasi, wawancara dan dokumentasi yang dianalisis dengan triangulasi, yaitu reduksi data-penyajian data dan penarikan kesimpulan. Results: The results of the service Teachers can use and utilize the independent teaching platform well and be creative in the work features that are implemented in classroom learning. Conclusions: The impact felt by the participants is very real, it can increase teacher confidence and teacher insight in implementing the independent curriculum which was initially confused. Limitations: the budget and teacher readiness. Contribution: This service is useful in the disciplines of education, education technology, literacy and information, education management, teacher professional development, and curriculum development.